Consumers' attitudes and their effects on electric vehicle sales and charging infrastructure construction: An empirical study in China. (June 2022) - Wang, Yuanyuan; Chi, Yuanying; Xu, Jin-Hua; Yuan, Yongke
Abstract: There are close links and interactions among consumers' attitudes, the construction of charging infrastructure, and the diffusion of new energy vehicles (NEVs). This study focuses on consumers' sentient attitudes toward charging infrastructure and the effect of consumer attitudes toward the construction of charging piles and NEV sales using natural language processing technology and the panel vector autoregressive method. Consumers' sentient attitudes (i.e., positive, negative, and neutral) were inferred by analyzing consumer comments on charging infrastructure obtained from the internet. The key reasons for consumers' negative attitudes were further investigated, and the diversity in their attitudes was explored at the city level. The results show a growing concern for consumers about charging infrastructure since 2013. The overall satisfaction of consumers has constantly improved. The top pain points that cause consumers' negative attitudes are inconvenient charging, charging dilemmas, inability to install private charging piles, etc. Consumers' negative attitudes have a significantly positive impact on the charging piles' construction. It also has a significantly negative impact on the sales of NEVs, but the effects are themselves short-term. Usually, the impact of negative attitudes is stronger than that of positive attitudes. Highlights: Negative attitude consumers focus on six pain points of charging infrastructure. The most comments focused on the charging scene "home", followed by "expressway". The more developed the cities, the higher the proportion of negative attitudes. Negative and positive attitudes have positive impact on charging pile construction. Negative attitudes have a greater impact on NEV sales than positive attitudes.